2017
DOI: 10.1037/emo0000272
|View full text |Cite
|
Sign up to set email alerts
|

What you like is what you try to get: Attitudes toward emotions and situation selection.

Abstract: Why do people expose themselves to certain emotional stimuli and avoid others? We propose that what people want to feel is linked to attitudes toward emotions. In 3 studies, we show that individuals with more (vs. less) negative attitudes toward an emotion were more (vs. less) likely to avoid stimuli that induce that emotion. People who evaluated disgust (or joy) less favorably than others were less likely to expose themselves to disgusting (or joyful) pictures (Study 1). These links were emotion-specific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
(58 reference statements)
1
20
0
1
Order By: Relevance
“…As Webb and colleagues noted in their meta-analysis, research on situation selection is far rarer than cognitive and response-based emotion regulation strategies (Webb, Miles, & Sheeran, 2012). Future research and other laboratories should therefore extend beyond this paradigm to test additional hypotheses about when positivity effects may or may not emerge (for research on situation selection in younger adults, see Markovitch, Netzer, & Tamir, 2017; Vujovic, Opitz, Birk, & Urry, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As Webb and colleagues noted in their meta-analysis, research on situation selection is far rarer than cognitive and response-based emotion regulation strategies (Webb, Miles, & Sheeran, 2012). Future research and other laboratories should therefore extend beyond this paradigm to test additional hypotheses about when positivity effects may or may not emerge (for research on situation selection in younger adults, see Markovitch, Netzer, & Tamir, 2017; Vujovic, Opitz, Birk, & Urry, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found positive relationships between people's attitudes towards a particular emotion and whether they choose to strive for, or engage with, that emotion (Markovitch et al, 2016(Markovitch et al, , 2017. Emotion regulation choice has also been found to be associated with people's self-reported and/or externally manipulated beliefs about particular emotions, such including how much control they believe they have over their emotions (e.g.…”
Section: Individual Determinantsmentioning
confidence: 99%
“…For example, if I know that I will become particularly engrossed in the emotions of other people, then I may be a bit more careful in terms of how I decide whether to even start potentially engrossing conversations in the first place. Research reveals that the use of situation selection depends on attitudes toward the emotion in question (Markovitch, Netzer, & Tamir, ), and on beliefs about how well one can control emotions (Rovenpor & Isbell, ). Situation selection can be quite useful, especially for those who are otherwise unskilled at emotion regulation (Webb, Lindquist, Jones, Avishai, & Sheeran, ), because it prevents an empathy‐eliciting situation from arising.…”
Section: A Motivated Emotion Regulation Approach To Empathymentioning
confidence: 99%